Maximum strength benchmarks for difficult static elements on rings in male elite gymnastics - Schärer, C.; Huber, S.; Bucher, P.; Capelli, C.; Hübner, K. (Sports, 2021)
On rings, in men`s artistic gymnastics, the general strength requirements for important static elements remain elusive. Therefore, the aim was to describe the relationship between a new conditioning strength test and a maximum strength test of static elements on rings in order to determine the minimal strength level (benchmarks) required to maintain these elements with one`s own body weight. Nineteen elite gymnasts performed a concentric (1RM isoinertial) and eccentric (isokinetic: 0.1 m/s) conditioning strength test for swallow/support scale (supine position) and inverted cross (seated position) on a computer-controlled device and a maximum strength test maintaining these elements for 5 s on rings with counterweight or additional weight. High correlation coefficients were found between the conditioning maximum strength for swallow/support scale (r: 0.65 to 0.92; p < 0.05) and inverted cross (r: 0.62 to 0.69; p > 0.05) and the maximum strength of the elements on rings. Strength benchmarks varied between 56.66% (inverted cross concentric) and 94.10% (swallow eccentric) of body weight. Differences in biomechanical characteristics and technical requirements of strength elements on rings may (inter alia) explain the differences between correlations. Benchmarks of conditioning strength may help coaches and athletes systematize the training of strength elements on rings.